Efficacy and safety of immune checkpoint inhibitors with or without radiotherapy in metastatic non-small cell lung cancer: A systematic review and meta-analysis - Liu, Zijing; Xu, Tiankai; Chang, Pengyu; Fu, Weijia; Wei, Jiaying; Xia, Chengcheng; Wang, Qiang; Li, Man; Pu, Xiaoyu; Huang, Fuxue; Ge, Chao; Gao, Yan; et al. (Frontiers in Pharmacology, 2023)
Background and purpose: Although immune checkpoint inhibitors (ICIs) have become the first-line treatment for metastatic non-small cell lung cancer (mNSCLC), their efficacy is limited. Radiotherapy (RT) can activate the systemic antitumor immune response by increasing the release of antigens from tumor tissues. Therefore, in patients with mNSCLC treated with ICIs, investigations were performed to determine whether the addition of RT improved the outcomes. Furthermore, the adverse events rate was evaluated. Methods and materials: Pubmed, Embase, and Cochrane Library were searched using the keywords “radiotherapy,” “immune checkpoint inhibitors,” and “non-small cell lung cancer” from the date of inception to May 2, 2022. RCTs and NRCTs comparing the efficacy and safety of RT combined with ICIs versus ICIs alone in metastatic NSCLC were assessed. The primary outcomes were progression-free survival (PFS) and overall survival (OS), and the secondary outcomes were abscopal response rate (ARR), abscopal control rate (ACR), adverse events rate, and pneumonia rate. Results: In 15 clinical studies, 713 patients received RT combined with ICIs and 1275 patients received only ICIs. With regard to PFS and OS, the hazard ratios of RT combined with ICIs were 0.79 (0.70, 0.89) and 0.72 (0.63, 0.82), respectively. In terms of ARR and ACR, the odds ratios (ORs) of RT combined with ICIs were 1.94 (1.19, 3.17) and 1.79 (1.08, 2.97), respectively. Furthermore, subgroup analyses of ARR and ACR signified that the combination therapy resulted in better local control of lesions outside the irradiation field in the hypofractionated RT, extracranial RT, and ICI-naïve subgroups. In terms of adverse events, the addition of RT did not significantly increase the adverse events rate but was associated with a higher pneumonia rate (OR values were 1.24 (0.92, 1.67) and 1.76 (1.12, 2.77), respectively). Conclusions: Meta-analysis of existing data suggests that the addition of RT can significantly prolong PFS and OS in patients with metastatic NSCLC receiving ICIs. In addition to lesions in the irradiation field, RT can improve the local control rate of lesions outside the irradiation field via immune activation. Combination therapy does not increase the overall risk of adverse reactions, except for pneumonia.